Book Review: The Technological State in Indonesia: The Co-constitution of High Technology and Authoritarian Politics. (July 2013) - Abraham, Itty
SULFIKAR AMIR (2013), The Technological State in Indonesia: The Co-constitution of High Technology and Authoritarian Politics . London and New York: Routledge. xviii, 190 pp. Hardcover.